Decolonizing The Learning Process In The English Language Education Study Program - Farid, Rezqan Noor; Aristia, Cendikia Flory; Rahmaniah, Sovia (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2024)
The English Education Study Program as a place of language learning is an institution where the paradigm of foreign language learning that is still thick with the practice of linguistic colonialism is likely to still take place. This study aims to reveal the existence of this paradigm in the teaching process in the study program as a material for future changes in order to achieve widespread and flexible learning. This change will also promote local culture in foreign language learning. This study uses qualitative descriptive method as a means of revealing the necessary facts. Interviews and observations of the learning process and the interaction between lecturers and students were used as data collection tools which were analyzed using the Interpretative phenomenological analysis (IPA) method. The findings of this study show that the phenomenon of language colonialization is still an aspect that lecturers and students are not aware of. Its existence in the context of teaching in the English department of the Faculty of Education is still at the stage of stratification of the language used as an introduction in class, unconscious restrictions on the use of certain languages, and the widespread use of certain languages over other languages.